Compliance Through Persuasion Not Force - Kashyap, Sonakshi (Trinity Law Review, 2021)
Our constitution guarantees to all citizens of India, the right to freely conduct any trade  or commerce. To realize this fundamental right, the state is required to ensure free  markets that run on principles of fair competition. The Competition Act, 2002 deals  with the regulation of competition in Indian markets, and the Competition Commission  of India (CCI) is the nodal agency which undertakes the enforcement of this Act. One  of the thrust areas of the Competition Act is ‘Competition Advocacy’, which aims at  building a competition friendly environment by creating awareness about the  importance of fair competition amongst the different stakeholders in a market place.  Competition advocacy, therefore, helps in creation of healthy markets, aware  consumers, ready compliance with competition law, and thereby reduces the burden of  CCI. Competition advocacy in foreign jurisdictions is usually carried out by  autonomous bodies through their involvement in early stages of policy making and  assessment of their potential impact on competition. The Indian law provides that it is  the duty of CCI to promote competition advocacy, and give its opinion on policy matters  affecting competition if the same is requested by governments at Central or State levels.  The CCI has undertaken various initiatives, like, research programmes, collaboration  with different institutions, etc. to effectively create awareness around fair business  practices. However, the Indian law is insufficient to adequately achieve the goal of  competition advocacy. The law, therefore, needs to be amended by giving more power  to CCI. CCI should be allowed to offer suo-moto opinions on policies that in its belief  affect competition, further such opinion should be given due significance and not  rejected without legitimate grounds being recorded for the same. Competition  advocacy, can also be improved by ensuring autonomy and transparency in functioning  of CCI, use of social media in creating public awareness, carrying out Regulatory  Impact Assessment (RIA) of policies etc.
Keywords: consumers; CCI; (RIA); advocacy; competition; institutions